SDGs DISCLOSURE IN PT BUKALAPAK.COM TBK'S SUSTAINABILITY REPORT FOR THE 2021-2023 PERIOD - Nurafni Oktaviyah; Samirah Dunakhir; Warka Syachbrani ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
The research aims to analyze the disclosure of Sustainable Development Goals (SDGs) in the PT Bukalapak.com Tbk sustainability report with a focus on compliance with Peraturan Otoritas Jasa Keuangan (POJK) No. 51/POJK.03/2017 for the period 2021 to 2023. POJK 51/POJK.03/2017 requires companies to prepare sustainability reports that cover relevant economic, social and environmental aspects, as well as disclose their contribution to the SDGs. This research evaluates the performance of PT Bukalapak.com Tbk in integrating SDGs in the company's sustainability report and how the company complies with the provisions regulated by POJK. Data was obtained through content analysis of sustainability reports with a focus on the SDGs-related disclosures that are most frequently disclosed and how detailed these disclosures are. The research results show that PT Bukalapak.com has integrated SDGs in their business strategy and reporting, with a significant increase in the quality and quantity of disclosure from year to year. SDGs goal 4 (education and training) is a priority in 2021 and 2022. Priority in 2023 is SDGs goal 1 (eliminate all forms of hunger). Compliance with POJK is generally quite good. full disclosure has been reported on most aspects over the past three years. Partial disclosure is reported on aspects of economic performance in 2022 and 2023. Apart from that, environmental performance also does not provide full disclosure. The total percentage of disclosure in 2021 and 2022 was 95.24% and in 2023 it decreased to 87.5%. Disclosure of SDGs in PT Bukalapak.com Tbk's sustainability report continues to develop, driven by regulations and increased corporate awareness of the importance of sustainability. These findings provide insight for stakeholders, including regulators, investors and companies, in understanding the important role of sustainability reporting in supporting the achievement of the SDGs.